Behind enemy lines: Expressing locomotor movements of athletes in the National Rugby League Women`s (NRLW) competition relative to opposition data - Minahan, C.; Thornton, H. R.; Bellinger, P.; Ward, J.; Lovell, D.; Buxton, S.; Newans, T. (Journal of Sports Sciences, 2023)
We provide a novel analysis of the locomotor movements of athletes in the National Rugby League Women`s (NRLW) competition by presenting the data of opposing teams expressed as a relative (%) difference and explore the association with match outcome. 117 rugby league athletes from the four NRLW clubs participated in this study. Mean speed (m·min-1), mean high-speed running (>12 km·h-1; m·min-1), and mean acceleration (m·s-2) were measured in 12 matches (370 individual match files) using the Global Navigation Satellite System (GNSS). Individual GNSS-derived data from each match-half were summed across each team and the association with total points and the points differential in each match-half was determined using linear mixed models. Greater high-speed running and lower mean acceleration were associated with more points being scored. A greater relative difference in mean high-speed running between competing teams was associated with a higher points differential. That is, if a team completed 10% more high-speed running than their opposition, they were likely to score an average of 3.2 points more during a given match-half. This unique analysis of GNSS-derived data may assist coaches and performance support staff to interpret the locomotor movements of female rugby league players with the appropriate considerations for the opposition team.